Institutional investors, risk management and audit committees influence on non-financial risk disclosure - Adibah Jamil; Mohamat Sabri Hassan; Norman Mohd Saleh; Rubayah Yakob (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study examines the complementary or substitution role of audit committee independence (ACInd), risk management committee (RMC) and institutional investors on non-financial risk disclosure (NFRD). While the existing literature provides inconclusive evidence on the individual influences of various monitoring mechanisms on NFRD, it is necessary to examine whether their combined monitoring roles are present as many monitoring mechanisms coexist within an organisation. This study examined a sample of 864 Bursa Malaysia companies from 2016 to 2018. The Delphi technique is used to finalise NFRD items. This study performed regression and simple slope tests to examine the complementary and substitutive role of ACInd, RMC and institutional investors. The findings show that RMC is substitutive to AcInd towards NFRD. This demonstrates that RMC has the expertise and potential to lessen any information asymmetry, making it the most reliable monitoring mechanism. These findings indicate the significance of establishing a standalone RMC among Malaysian companies to supervise the NFRD reporting.